Fresno County Bar Association and Rotary Club Luncheon with State Bar President Anthony Murray - Watkins, Howard::::::::: (1983)
Post luncheon with attorneys gathering at head table; Ed Fanucchi in plaid coat, James Thaxter in middle; Robert Wash at far right